Urgensi Pendaftaran tanah (Perspektif Utilities dan Kepastian Hukum) - ochtorina susanti (Warmadewa Press, 2017)
ABSTRACT The land registry is an administrative liability based on legislation that has two goals: on the side of the utilities and in terms of legal certainty, which boils down to guarantee protection. When later raised legal act which implies the land ownership dispute, it can be proved by evidence that is perfect evidence, namely the certificate of land ownership. This study aims to find and analyze and provide an understanding of the importance of land registration in Indonesian positive law. Results of studies using normative juridical with legislation approach and conceptual approach. On the side of legal certainty and these utilities provide an explanation that land registration is done in order to provide legal certainty for the public welfare. Keyword : Registration, Land, Utilities, Legal Certainty